A fault tolerant switched reluctance motor drive for electric vehicles under multi-switches open-fault conditions. (November 2020) - Yang, Qingqing; Wang, Rui; Ma, Mingyao; Yang, Shuying; Zhang, Xing
Abstract: A power converter with effective fault-diagnosis and fault-tolerant control can improve the reliability of switched reluctance motor drive system (SRD). At present, there are many research results on single power switch fault. In view of the multi-switches faults caused by the harsh operational environments and repetitive duty cycles, this paper presents a flexible fault-tolerant topology with fault-diagnosis, fault-tolerant control strategy for diverse open-circuit faults occurring in the SRD under different working conditions, and the common H-bridge has been selected as the fault-tolerant topology. When the SRD is subjected to open-circuit faults, the fault-diagnosis can be achieved by detecting the characteristic of the real-time phase currents, and then the faulty switches can be replaced automatically by the corresponding reverse ones to sustain the driving operation with further optimized output torque. Highlights: The H-bridge topology is used as the fault-tolerant drive structure for the switched reluctance motor driving system. Fault-diagnosis, fault-tolerant control strategy of the multi-switches faults for the H-bridge. The current characteristics of the faulty phases are analyzed. Fault-diagnosis can be carried out on-line in real time. The redundant switches in H-bridge are fully utilized for fault-tolerant control. The feasibility and effectiveness of the proposed control method are verified by simulation and experiment.